FUNCTION: PEMBELAJARAN BERBASIS EKSPLORASI - Harvanessa Aprilia; Sidhi Wiguna Teh (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
Several studies stated that the learning style of the millennials dominates visually and kinesthetically, approaching group system or communities wherein millennials generally enjoy the interaction and sharing learning environments rather than reading books. This generation is described as a generation that is fast and practical, looking for fun, technology savvy but also categorized as a generation that is dependent on technology and has a short attention span. With the development of this instant society, not a few among the milenial that do not appreciate the process, instead they focus on directly jumping onto the final results, wherein the quality of a process does not only determines the quality of the final result but it actually triggers a sense of ownership and respect for what is being produced. Based on the results of the research that has taken place, a creative space is needed to provide the younger generation for devoting their creativity through the whole process. Makerspace contains self-made aspects that trigger ownership and sharing as well as experiments that are compatible with working and learning styles of millennials. Makerspace is a program that is considered not only suitable but also popular in the creative industry world and is very attractive to the generations of millennials in creativity aspects. Combining science, art, and aesthetics which will not only support the process of thinking in the world of education but as well as raise their moral values such as respect. It is essential to be able to appreciate every process that goes through as learning, both the process of work done personally and in groups.AbstrakDalam beberapa literatur menyatakan bahwa learning style generasi milenial lebih mendominasi secara visual dan kinestetik, mengarah kepada komunitas, sehingga umumnya mereka lebih menikmati interaksi dan sharing learning environment dari pada membaca buku.  Generasi ini dideskripsikan sebagai generasi yang serba cepat dan praktis dalam mencari kesenangan. Cerdas teknologi tetapi juga dikategorikan sebagai generasi yang tergantung pada teknologi, serta memiliki rentang perhatian yang pendek. Dengan perkembangan yang serba instan, tidak sedikit dari generasi milenial yang kurang menghargai proses dan hanya berfokus pada hasil akhir, padahal kualitas sebuah proses tidak hanya menentukan kualitas hasil akhir tapi juga memicu rasa kepemilikan dan rasa menghargai terhadap apa yang dihasilkan. Berdasarkan hasil studi yang telah berlangsung, maka dibutuhkan wadah dimana generasi muda dapat mencurahkan kreativitasnya melalui proses. Makerspace mengandung unsur self-made yang memicu rasa kepemilikan dan unsur sharing, serta experiment yang sesuai dengan working and learning style of millennials. Makerspace merupakan salah satu program yang dianggap bukan hanya cocok namun juga sedang popular didunia industri kreatif dan sangat menarik perhatian generasi milenial dalam aspek kreativitas.  Mengkombinasi antara ilmu pengetahuan, seni dan estetika tidak hanya akan mendukung proses berfikir dalam dunia pendidikan namun juga meningkatkan nilai-nilai moral seperti menghargai. Mampu menghargai setiap proses yang dilalui sebagai pembelajaran, baik proses pengerjaan yang dilakukan pribadi maupun kelompok.